1993
DOI: 10.1063/1.110340
|View full text |Cite
|
Sign up to set email alerts
|

Self-limited layer-by-layer etching of Si by alternated chlorine adsorption and Ar+ ion irradiation

Abstract: We report the observation of self-limited layer-by-layer etching of Si by alternated chlorine adsorption and low energy Ar+ ion irradiation using an ultraclean electron-cyclotron-resonance plasma apparatus. The etch rate per cycle increased with the chlorine supplying time and saturated to a constant value of about 1/2 atomic layer per cycle for Si(100) and 1/3 for Si(111), which was independent of the chlorine partial pressure in the range of 1.3–6.7 mPa. These results indicate that etching was determined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 5 publications
1
72
0
Order By: Relevance
“…Upon increasing substrate bias voltage, the etch rates increased rapidly with increased amounts of higher-order etch products (SiCl 3 , SiCl 4 ). Matsuura et al 22 and Suzue et al 32 reported on "self-limited layer-by-layer etching" and "selflimited atomic layer etching" of Si, respectively, using ECR plasmas. The etch rate per cycle increased with the chlorine exposure time and saturated to a constant value of about 1 2 and 1 3 of a monolayer per cycle for Si(100) for Si(111), respectively, independent of the chlorine partial pressure.…”
Section: The Early Days Of Atomic Layer Etchingmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon increasing substrate bias voltage, the etch rates increased rapidly with increased amounts of higher-order etch products (SiCl 3 , SiCl 4 ). Matsuura et al 22 and Suzue et al 32 reported on "self-limited layer-by-layer etching" and "selflimited atomic layer etching" of Si, respectively, using ECR plasmas. The etch rate per cycle increased with the chlorine exposure time and saturated to a constant value of about 1 2 and 1 3 of a monolayer per cycle for Si(100) for Si(111), respectively, independent of the chlorine partial pressure.…”
Section: The Early Days Of Atomic Layer Etchingmentioning
confidence: 99%
“…Steps 2 and 4 are purge steps. Since then, a large set of publications has appeared in scientific literature and the method has come to be known by a variety of other names, namely digital etching, 21 layer-by-layer etching, 22 molecular-layer etching, 23 plasma atomic layer etching (PALE), 24 etc. Yet, the original name of "atomic layer etching" coined in the first patent has remained most popular.…”
Section: The Early Days Of Atomic Layer Etchingmentioning
confidence: 99%
“…Versions of these tests have appeared in ALE studies, 39,47,48 although not necessarily called out or in context to one another. These tests can help indicate to what degree the ALE process approaches ideal behavior, albeit nonideal conditions may still yield significant benefit.…”
Section: Characterization Testsmentioning
confidence: 99%
“…For chlorine adsorption on a room temperature silicon substrate, Langmuir self-limited adsorption of about one monolayer of chlorine is typically seen. 81,82 Matsuura et al 83 found a self-limited layer-by-layer etching mechanism with the substrate at room temperature using Cl 2 exposure followed by low energy (20 eV) Ar ion bombardment in an ECR system. An etch depth of 0.5 atomic layer per cycle was achieved which increased with Cl 2 exposure of the surface.…”
Section: Iii-v: Gaasmentioning
confidence: 99%